FETAL CEREBROPLACENTAL RATIO AT TERM PREGNANCY AS A PREDICTOR OF ADVERSE PERINATAL OUTCOME - Singh, Kirti; Acharya, Neema; Singh, Priyanka; Phatak, Suresh V (International Journal of Psychosocial Rehabilitation, 2020)
The middle cerebral artery (MCA) Doppler accuracy for predicting fetus at risk of wellbeing is not known properly. The study’s objective is to is to evaluate the middle cerebral artery Doppler accuracy for predicting adverse fetal outcome. For studying perinatal outcome in pregnancy at term with normal cerebroplacental ratio,to study perinatal outcome in pregnancy at term with abnormal cerebroplacental ratio,to compare between the perinatal outcomes in pregnancy at term with normal and abnormal cerebroplacental ratio. A cross sectional study including 1000 pregnant women at term between 37 to 40 weeks of gestation. CPR (Pulsatility index of MCA and PI of UA) were calculated of all patients on USG Doppler. Abnormal CPR were related to bad fetal outcome. 1000 women will be studied. The obstetric intervention rate for suspected fetal distress will be higher among cases with lower CPR compared to those with normal CPR. A significantly higher rate of adverse perinatal outcome will be found in fetuses with CPR < 10th percentile compared to those with CPR ≥ 10th percentile. Data will show, low risk term pregnancies with reduced CPR has association with more risk of obstetric intervention because of fetal distress and bad fetal outcomes. Earlier detection of low CPR can be helpful in predicting adverse perinatal outcomes.